Numerical investigation on wheel-turnout rail dynamic interaction excited by wheel diameter difference in high-speed railway - Chen, Rong; Chen, Jia-yin; Wang, Ping; Xu, Jing-mang; Xiao, Jie-ling (Journal of Zhejiang University. A. Science, 2017)
The wheel-rail relationship in turnout is more complicated than that in ordinary track. Profile wear and machining errors of the wheelset cause deviations Of the rolling radius on different wheels. Therefore, wheelsets move to the direction of smaller diameter wheels in search of a new stable state and to change the condition before entering the turnout. Thc main aim of the present work is to examine the wheel-turnout rail dynamic interaction combined with the static contact behaviour. Calculations are performed on a high-speed vehicle CRH2 and the No. 12 turnout of the passenger dedicated line. The wheel-turnout contac! geometric relationship and normal contact behaviour under wheel diameter difference are assessed by the trace principle and finite element method. A high-speed vehicle-turnout coupling dynamic model is established based on SIMPACK software to analyse the wheel-rail dynamic interaction, riding comfort, and wear. Both the wheel diameter amplitudes and distribution patterns are accounted for. The simulation shows that wheel diameter difference can greatly disturb the positions＇ variation of wheel-rail contact points and affect the normal contact behaviour on switch rails by changing the load transition position. The effect of wheel diameter diffierence on wheel-turnout rail dynamic interaction can be divided into three according to its amplitude： when the wheel diameter difference is within 0-1.5 mm, the wheel flange comes into contact with the switch rail in advance, causing a rapidly increased lateral wheel-rail force; when it is within 1.5 2.5 mm, trains are subject to instability under equivalent in-phase wheel diameter difference; when it is larger than 2.5 mm, the continuous flange-switch rail contact helps strengthen the vehicle stability, but increases the wheel-rail wear. It is recommended to control the wheel diameter difference to within 2.5 mm but limit it to 2 mm if it is distributed in-phase.